2022
DOI: 10.1186/s12955-022-01928-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the 15-item Geriatric Depression Scale (GDS-15) into Igbo language: a validation study

Abstract: Background Late-life experiences such as protracted and indisposing medical disorders can negatively impact older adults’ psychological and mental health, making them vulnerable to depression. Majority of the assessment tools for depression were developed for use in western countries. There is therefore the need for availability of culture- and environment-specific tools for assessment of depression in low-and-middle-income countries. This study was designed to cross-culturally adapt and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“… 25 A prevalence of 45% had been reported among older adults from a healthy population, 13 thus, necessitating the validation of the geriatric depression scale for use amongst this population. 26 Stroke patients might exhibit high intolerance of their disability and uneasiness to cope with the challenge, thus, the tendency to experience lots of psychological problems such as depression. 25 Evidence shows that depression is a common complication of stroke, resulting in high morbidity and mortality, 27 and approximately 40% to 50% of patients experience depression.…”
Section: Discussionmentioning
confidence: 99%
“… 25 A prevalence of 45% had been reported among older adults from a healthy population, 13 thus, necessitating the validation of the geriatric depression scale for use amongst this population. 26 Stroke patients might exhibit high intolerance of their disability and uneasiness to cope with the challenge, thus, the tendency to experience lots of psychological problems such as depression. 25 Evidence shows that depression is a common complication of stroke, resulting in high morbidity and mortality, 27 and approximately 40% to 50% of patients experience depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Nigeria, Africa’s most populous nation, have reported a high prevalence rate of depression among older adults, 81 and also provided a validated culture-specific tool for measuring depression. 82 …”
Section: Discussionmentioning
confidence: 99%
“…This procedure was also followed in other studies. 31 , 32 It was also ensured that one of the forward translators had no medical background and that 3 of the translators were blinded about the concept of the instrument. This was to reduce the possibility of bias in the translation.…”
Section: Discussionmentioning
confidence: 99%